Low birth weight is associated with increased fat intake in school-aged boys. Issue 11 (17th May 2018) - Bischoff, Adrianne R.; Portella, André K.; Paquet, Catherine; Dalle Molle, Roberta; Faber, Aida; Arora, Narendra; Levitan, Robert D.; Silveira, Patrícia P.; Dube, Laurette
Abstract: Evidence suggests that both high and low birth weight children have increased the risk for obesity and the metabolic syndrome in adulthood. Previously we have found altered feeding behaviour and food preferences in pre-school children and adults born with low birth weight. In this study, we investigated if birth weight was associated with different intake of fat, carbohydrate and/or protein at 6–12 years of age. This is a cross-sectional study where 255 guardians answered online and telephone questions including anthropometrics and demographic data, parental family food rules (food control, encouragement and restriction) and a complete web-based FFQ for their children (130 boys and 125 girls). Baseline demographic and parental food rules characteristics did not differ accordingly to sex. Linear regression models were conducted separately for each sex, adjusted for income, age and maternal age. There were no differences in total energy intake, but energy density (ED, energy content/g) was negatively associated with birth weight in boys. Macronutrient analysis showed that ED intake was from a greater intake of fat. Birth weight was not a significant predictor of protein and carbohydrate intake in boys. In girls, we saw a positive correlation between fat intake and cholesterol intake v . birth weight, but no association with ED intake (results did not remain after adjustment). The study shows that low birth weight is associated with altered fat intake in childhood in a sex-specific manner. It is likely that biological factors such as fetal programming of homoeostatic and/or hedonic pathways influencing food preferences are involved in this process.